Home » Aptitude » Algebra » Question
  1. If x = √5 + 2 ,then the value
    2x2 - 3x - 2
    is equal to
    3x2 - 4x - 3

    1. 0.185
    2. 0.525
    3. 0.625
    4. 0.785
Correct Option: C

Expression =
2x2 - 3x - 2
3x2 - 4x - 3

Expression =
2(√5 + 2)2 - 3(√5 + 2) - 2
3(√5 + 2)2 - 4(√5 + 2) - 3

Expression =
2(5 + 4 + 4√5) - 3(√5 + 2) - 2
3(5 + 4 + 4√5) - 4(√5 + 2) - 3

Expression =
18 + 8√5 - 3√5 - 6 - 2
27 + 12√5 - 4√5 - 8 - 3

Expression =
10 + 5√5
16 + 8√5

Expression =
5(2 + √5)
8(2 + √5)

Expression =
5
= 0.625
8



Your comments will be displayed only after manual approval.